ВИКЛАДАННЯ ДИСЦИПЛІНИ "БІОФІЗИКА” ДЛЯ СТУДЕНТІВ ПРИРОДНИЧОГО ФАКУЛЬТЕТУ У КОНТЕКСТІ ВИМОГ БОЛОНСЬКОГО ПРОЦЕСУ (Педагогіка вищої та середньої школи, 2007)
The Ukraine joining the Bologna process requires the reformation of higher education and development of the syllabus on "Biophysics" in accordance with European Standards. The implementation of the Credit and Accumulation System enables both a student and a teacher to check the grade accumulation during the studying of the subject and be concentrated on the achievements of target results.